Remodelling and Treatment of the Blood-Brain Barrier in Glioma - Wang, Yihao (Cancer Manag Res, 2021)
The blood-brain barrier (BBB) is an essential structure of the central nervous system (CNS), and its existence makes the local internal environment of the CNS a relatively independent structure distinct from other internal environments of the human body to ensure normal physiological and high stability of activities of the CNS. Changes in BBB structure and function are fundamental to the pathophysiology of many diseases. The occurrence and development of glioma are often accompanied by a series of changes in the structure and function of the internal environment, the most significant of which is remodelling of the BBB. The remodelling of the BBB usually leads to changes in the permeability of local microvessels, which provide certain favourable conditions for the occurrence and development of glioma. Meanwhile, the newly generated abnormal blood vessels and the remaining intact regions of the BBB also hinder the effects of drug treatments. Changes in permeability and structural function often lead to the creation of abnormally functioning vascular regions, which pose further treatment challenges. At present, therapeutic methods for glioma have not achieved satisfactory effects in clinical practice, and emerging therapeutic methods have not yet been widely used in clinical practice. In this review, we summarize the knowledge of remodelling of the BBB in the glioma environment, the type of changes that occur, and current BBB treatment methods and prospects for the treatment of glioma.